Communal riots and women victims - Gokilvani, S. (Srinivasan), 1957-; Subha, S. (New Delhi : Regal Publications, 2009)
Study of Kandadevi Swarnamoortheswarar Temple chariot dispute, Tamil Nadu, India.
Includes index.
Includes bibliographical references (p. [142]-148)
Keywords: Kandadevi Temple; Fasts and feasts -- India -- Kandadevi (Village); Hindu women -- Religious life -- India -- Kandadevi (Village); Ethnic conflict -- India -- Kandadevi (Village); Communalism -- India -- Kandadevi (Village); Tamil Nadu (India) -- Religion